Liquefaction-Induced Lateral Displacement and Settlement Mapping for Yogyakarta-Bawen Toll Road Section I & II, Indonesia - Paulus Kevin; Muhrozi Muhrozi (Civil Engineering Dimension, 2023)
The liquefaction-induced ground displacement (the lateral displacement and ground settlement) study in the Yogyakarta-Bawen toll road, Indonesia, is not yet conducted as the importance of this project, the project needs to be mapped. In this study, the mapping is conducted using two methods for lateral displacement, Gillins & Bartlett’s method and Zhang et al.’s method, while the mapping of ground settlement using Tokimatsu & Seed’s method and Yoshimine’s method. For Gillins & Bartlett’s method, the lateral displacement map in Yogyakarta-Bawen is dominated by moderate to high categories in section I but relatively low in section II. Meanwhile, Zhang et al.’s map in the I & II sections of the toll road is relatively dominated by the moderate category. Furthermore, the ground settlement map in I & II sections with Tokimatsu & Seed is mostly categorized as very high meanwhile Yoshimine’s map is predominately classified as low to moderate.